The very early-succession herbaceous vegetation in the ‘Vaia’ windstorm clearings within the Italian southeastern pre-Alpine mountain belt (Veneto and Trentino) - Tasinazzo, Stefano (Hacquetia, 2023)
The very early herbaceous vegetation which established in the clearings following 2018 ‘Vaia’ storm was investigated in some pre-Alpine areas of Northeast Italy, on calcareous as well as acidic substrata. Sixty-two original vegetation-plot records were executed in spruce or mixed beech-silver fir-spruce blowdown forests, within two years after the salvage logging had been completed. According to different origin and degree of soil disturbance, different communities were recognised. Galeopsis pubescens and G. tetrahit rich stands develop as ephemeral annual associations at the beginning of the regeneration succession where partially decomposed coniferous needles and twigs have accumulated in the litter. Soils with altered profiles due to forestry machineries harbour dominance of perennial herbaceous species (especially Senecio nemorensis agg., Atropa bella-donna, Epilobium angustifolium) as many already recognised associations or vegetation types we ascribed to community level. All coenoses belong to Epilobietea angustifolii class, with the exception of Calamagrostis arundinacea-rich stands on undisturbed base-rich as well as base-poor soils, whose syntaxonomic positions are unclear.